Russian" Israel and Russia - A. V. Fedorchenko (Vestnik MGIMO-Universiteta)
Morozov V.M. "Russian" Israel: the impact of immigrants on Russian-Israeli relations. Moscow: MGIMO- University, 2015. 165 p.